Effect of substrate on the electro chromic properties of tungsten trioxide thin films - Prabhakar, Vidya; P, Ashrit (International Journal of Engineering and Technology, 2014)
Thin films of tungsten trioxide (WO3) were deposited onto glass and Indium Tin Oxide (ITO) coated glass substrates using thermal evaporation technique under various deposition conditions. In the present work the effect of substrate on the structure and EC performance of WO3 thin films has been examined using a dry lithiation method. The structural and optical changes occurring in these films with lithium insertion have been studied. It is found that the ITO coated substrate promotes the granulation and higher coloration efficiencies of the films. The peak efficiency is observed at higher infrared wavelengths where it is principally the reflectance modulation that brings about optical changes. Keywords: WO3 Thin Films, Electrochromism, Optical and Structural Properties, Effect of ITO Substrate.